1983
DOI: 10.1111/j.1471-4159.1983.tb11827.x
|View full text |Cite
|
Sign up to set email alerts
|

Regional Distribution of Methionine‐Enkephalin‐Arg6‐Phe7 in the Rat Brain: Comparative Study with the Distribution of Other Opioid Peptides

Abstract: The distribution of the opioid peptide methionine-enkephalin-arginine6-phenylalanine7 (M-Enk-Arg6-Phe7) has been investigated in various structures of the rat brain by using a highly specific radioimmunoassay (RIA). Immunoreactive M-Enk-Arg6-Phe7 has been further characterized by high performance liquid chromatography. The levels of M-Enk-Arg6-Phe7 in various structures of the rat brain were compared with the levels of several other opioid peptides, including methionine-enkephalin (M-Enk), leucine-enkephalin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(21 citation statements)
references
References 27 publications
2
19
0
Order By: Relevance
“…However, the neural lobe also contains consider¬ able amounts of Met-enkephalin (Giraud, Castañas, Patey et al 1983). Met-enkephalin itself is inactive at opioid receptors, the sole opioid receptor type in the neural lobe (Herkenham, Rice, Jacobson & Rothman, 1986), but one extended form of Metenkephalin which is present in the neural lobe does have high affinity for opioid receptors (Castañas, Bourhim, Giraud et al 1985;Bicknell, 1991).…”
Section: Discussionmentioning
confidence: 98%
“…However, the neural lobe also contains consider¬ able amounts of Met-enkephalin (Giraud, Castañas, Patey et al 1983). Met-enkephalin itself is inactive at opioid receptors, the sole opioid receptor type in the neural lobe (Herkenham, Rice, Jacobson & Rothman, 1986), but one extended form of Metenkephalin which is present in the neural lobe does have high affinity for opioid receptors (Castañas, Bourhim, Giraud et al 1985;Bicknell, 1991).…”
Section: Discussionmentioning
confidence: 98%
“…It has been previously demonstrated that MOP activation is mainly involved in acute pain relief (Matthes et al, 1996) while DOP activation was shown to decrease chronic pain (Gaveriaux-Ruff et al, 2011). The physiological ligands of MOP and DOP are beta-endorphin, endomorphin-1 and -2 as well as the most abundant pentapeptides Met and Leuenkephalins (Giraud et al, 1983). We decided to test in models of neuropathic pain the efficacy of these latter pentapeptides which are locally released under nocifensive stimuli (Yaksh et al, 1981;Bourgoin et al, 1986;Schreiter et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…The column was pre-equilibrated with 0-25 M-triethylammonium formate, pH 3 1, and eluted with a discontinuous gradient from 0 to 50% acetonitrile in buffer with a flow rate of 1 ml/min. Synthetic peptides were used as calibration standards (see Giraud, Castanas, Patey, Oliver & Rossier, 1983, for details). Fractions of 1 ml were evaporated in a Speed-Vac concentrator (Savant Instrument, Hicksville, NY) and resuspended in 50 mM-Tris HCl buffer, pH 8-4, containing 2 mM-CaCl2.…”
Section: Gel Filtrationmentioning
confidence: 99%